Third TRIPLE ThatCamp on Sustainability in Open Science (Pubmet, 2022)
Sustainability is easily one of the most pressing matters and most discussed topics of our time. This is as true for the economy and society as it is for research and thereby for Open Science. At the third TRIPLE ThatCamp we want to discuss and brainstorm on the relationship between sustainability and Open Science with you. If you are a researcher, a librarian, an interested citizen or someone otherwise involved or interested in sustainability in Open Science you are welcome to join us at this event.Topics of discussion could be:▸ How can the long-term quality of data be secured?▸ What governance/business models are sustainable for Open Science?▸ How do tools and services that have been developed within the life span of Open Science projects live on after?▸ Do training sessions provide sustainability?▸ How can we ensure sustainability in scholarly communication?▸ Any other topic that crosses your mind!